Addressing environmental impact assessment challenges in Pacific island countries for effective management of deep sea minerals activities. (September 2018) - Bradley, Melanie; Swaddling, Alison
Abstract: Environmental impact assessment (EIA) is an important instrument for management of deep sea minerals (DSM) activities in the Pacific islands region. However, effective EIA application is likely to be impeded by four challenges common among Pacific island countries: (1) human resource shortfalls; (2) insufficient quality control exercised over EIA reports; (3) weak compliance monitoring and enforcement; and (4) low levels of public engagement and participation in EIA. This paper identifies options for addressing the challenges, to improve EIA implementation and to ensure DSM activities are subject to appropriate regulation and oversight. Risks may be faced if the challenges are not addressed, including, failure to meet environmental management and governance obligations; loss of confidence in the regulatory system; environmental harm; and discouragement of sustainable development and investment. Pacific island countries that choose to engage with the DSM sector must apply EIA rigorously and continually work at improving their EIA systems, if they seek to maximise positive development outcomes and to minimise adverse effects on other marine users and values. Highlights: Deep sea minerals (DSM) activities should undergo environmental impact assessment (EIA). Effective EIA in Pacific island countries is impeded by challenges. Challenges must be addressed to strengthen EIA and to regulate DSM activities effectively. Sustainable development will be dependent on improving EIA processes.